PENDIDIKAN KARAKTER DALAM CERITA RAKYAT SULAWESI SELATAN “I LAURANG SI MANUSIA UDANG” KARYA H. ABDUL MUTHALIB (KAJIAN SASTRA ANAK) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The purpose of this research is to find out the educational values ​​and character of the characters in the folklore I Larang The Shrimp Man by H. Abdul Muthalib. This type of research is descriptive qualitative. The data of this research concerns words, sentences, expressions that contain the value of character education contained in the folklore I Larang The Shrimp Man. The data collection technique used in this study was a note-taking technique, namely reading and studying the texts of the folklore to be studied, then recording data or information that was in accordance with this research. In analyzing the research data, a study of children's literature was used with a pragmatic approach. The pragmatic approach is an approach that views literature as a means to convey certain goals to the reader. The results of the study show that the folklore I Larang Si The Shrimp Man contains character education values, namely, hard work, creativity. democracy, love of the motherland, and responsibility. Apart from these character education values, several characters from each character are responsible, creative, obedient and obedient, pious, envious, fair and wise.